2017
DOI: 10.1111/jdi.12761
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter 2 inhibitor, tofogliflozin, shows better improvements of blood glucose and insulin secretion in patients with high insulin levels at baseline

Abstract: Aims/IntroductionSodium glucose cotransporter 2 (SGLT2) inhibitors are a new class of drugs for the treatment of type 2 diabetes mellitus that improve control of plasma glucose and bodyweight, giving great hope for the clinical utility of these agents. However, it is unclear for which patients SGLT2 inhibitors will be useful.Materials and MethodsWe analyzed data from long‐term tofogliflozin monotherapy in an open‐label, randomized controlled trial in Japanese patients with type 2 diabetes mellitus. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Although insulin secretion is known to be induced by GLP-1 receptor agonists, it may be enhanced by SGLT2 inhibitors, possibly through different mechanisms, including the attenuation of glucotoxicity and improvement of insulin resistance. It has been reported that a SGLT2 inhibitor, tofogliflozin, increases insulin secretion especially in patients with high insulin levels at the baseline, suggesting that SGLT2 inhibitors may facilitate the recovery of β-cell dysfunction when the insulin secretion capacity is preserved to a certain extent (16). Consistently, both insulin resistance and secretion were improved in our patient.…”
Section: Discussionsupporting
confidence: 84%
“…Although insulin secretion is known to be induced by GLP-1 receptor agonists, it may be enhanced by SGLT2 inhibitors, possibly through different mechanisms, including the attenuation of glucotoxicity and improvement of insulin resistance. It has been reported that a SGLT2 inhibitor, tofogliflozin, increases insulin secretion especially in patients with high insulin levels at the baseline, suggesting that SGLT2 inhibitors may facilitate the recovery of β-cell dysfunction when the insulin secretion capacity is preserved to a certain extent (16). Consistently, both insulin resistance and secretion were improved in our patient.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the present subgroup analysis are consistent with what is observed in clinical practice, in that a significant reduction in HbA1c was shown with ipragliflozin treatment in patients with BMI ≥30 kg/m 2 . Although we did not identify a strong correlation between bodyweight reduction and improvement in HbA1c in the present study, such a correlation has been reported previously for another SGLT2 inhibitor, tofogliflozin. In that study, patients were divided into tertiles according to baseline insulin levels, and a correlation between improvement in glucose control and reduction in bodyweight was observed, but only in the tertile with the highest fasting insulin level.…”
Section: Discussioncontrasting
confidence: 80%
“…In fact, HDL-C is one of the components for classification of metabolic syndrome. Similarly, beneficial effects on glycemic control have been observed with higher BMI compared with lower BMI in Japanese phase III trials of SGLT2is 23,24 . Similarly, beneficial effects on glycemic control have been observed with higher BMI compared with lower BMI in Japanese phase III trials of SGLT2is 23,24 .…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, HDL-C and BMI in the Discontinuation group were significantly negatively correlated (r = -0.27, P < 0.05; Figure 3b). Similarly, beneficial effects on glycemic control have been observed with higher BMI compared with lower BMI in Japanese phase III trials of SGLT2is 23,24 . An additional glucoselowering effect due to the improvement in insulin resistance or sensitivity is expected to be larger when SGLT2 inhibitors are administered in patients with higher BMI.…”
Section: Discussionmentioning
confidence: 86%